Damage to construction, force majeure and earthquakes - Pizarro Wilson, Carlos (Revista de Derecho - Pontificia Universidad Católica de Valparaíso, 2010)
This work aims to determine the liable parties regarding defects and failures in the construction process and to establish their passive legal standing and the liability grounds; asserting the objective nature of said liability, that can be excluded within the framework of the delivery of works without defects and force majeure, notion that is contrasted to the natural phenomena of an earthquake, because the earthquake is different from its consequences, in order to clarify its application or exclusion as exoneration cause.